The behavioral, psychological, and social impacts of team sports: a systematic review and meta-analysis - Zuckerman, S. L.; Tang, A. R.; Richard, K. E.; Grisham, C. J.; Kuhn, A. W.; Bonfield, C. M.; Yengo-Kahn, A. M. (The Physician and Sportsmedicine, 2021)
Objectives: To assess the association between team sport participation and behavioral, psychological, and social health outcomes in young athletes.